Kajian Unsur Hara Tanah Sawah Untuk Menentukan Tingkat Kesuburan - I NYOMAN PUJA; A.A. NYOMAN SUPADMA; I MADE MEGA (Agrotrop : Journal on Agriculture Science, 2013)
Study on Soil Nutrients in Rice Field to Determine Soil Fertility Status.Research of soilnutrients in rice field to determine soil fertilitystatus had been done on rice field in district Penebel,Tabanan regency.This study aimed to assess level of soil fertility status on rice field.The research wasconducted by survey and laboratory analysis. The study consists of several stages such as, the formationof the land unit based on the compilation maps of soil type, geology and slope.It’s obtained 11 landunits. Each unit tookone samples. The soil sample was analyzed for Cation Exchange Capacity andCation Saturated (NH4OAC extractional pH 7,0); N-Total (Kjeldhal); P-total and K-total (HCl 25% extraction); Salinity (EC), Organic matter(Wokly and Black)and pH (H2O)(1 : 2,5). The analysisproceseshave done at Soil laboratory, Faculty of Agriculture, Udayana University.The result oftheresearch show that status of soil fertilityon rice field at district Penebel, Tabanan regency are low1.478,551ha (29.16%), medium2.286,721 ha (63.83%), and high2.286,721 ha (6.01%).